INVESTIGATING IMPACT OF SERVICE AND HYGIENE ON HOTEL REPUTATION DURING THE COVID -19 PANDEMIC : A PERSPECTIVE SIGNALING THEORY - Juliana Juliana; Amelda Pramezwary; Madeline Madeline; Nadya Valerie; Sylena Teresia Andrian; Venty Ventyani (Jurnal Hospitality dan Pariwisata, 2021)
Providing good service to consumers by a company can create customer satisfaction. Two aspects of service quality that play a significant role, in this case, our hotel services and hotel cleanliness. To get around this, entrepreneurs engaged in this field are increasingly competitive in improving service quality, which can meet consumers' needs and desires so that they can compete and develop in competitive conditions. In this study, researchers used the variable dimensions of service quality and hotel cleanliness as The variables that are expected to explain a hotel's good and bad reputation. This study aimed to analyze the effect of hotel services and hotel cleanliness on hotel reputation. This research method is descriptive quantitative with the type of research explanation. This study's population was hotel visitors in Tangerang, with a final sample of 157 respondents selected by the non-probability sampling technique. Methods of data analysis using PLS-SEM. The research shows that the higher the hotel services application will not affect the hotel's reputation during the Covid 19 pandemic. In comparison, the higher the application of hygiene involves the hotel's importance because, during the Covid 19 pandemic, the application of CHSE is the most important in maintaining the reputation of the hotel.Keywords: Hotel Service, Hygiene, Hotel Reputation